From outburst to quiescence: spectroscopic evolution of V1838 Aql imbedded in a bow-shock nebula. Issue 2 (8th April 2019) - Hernández Santisteban, J V; Echevarría, J; Zharikov, S; Neustroev, V; Tovmassian, G; Chavushyan, V; Napiwotzki, R; Costero, R; Michel, R; Sánchez, L J; Ruelas-Mayorga, A; Olguín, L; et al.
Abstract: We analyse new optical spectroscopic, direct-image and X-ray observations of the recently discovered a high-proper motion cataclysmic variable V1838 Aql. The data were obtained during its 2013 superoutburst and its subsequent quiescent state. An extended emission around the source was observed up to 30 d after the peak of the superoutburst, interpreted it as a bow shock formed by a quasi-continuous outflow from the source in quiescence. The head of the bow shock is coincident with the high-proper motion vector of the source ( v ⊥  = 123 ± 5 km s −1 ) at a distance of d  = 202 ± 7 pc. The object was detected as a weak X-ray source (0.015 ± 0.002 counts s −1 ) in the plateau of the superoutburst and its flux lowered by two times in quiescence (0.007 ± 0.002 counts s −1 ). Spectroscopic observations in quiescence we confirmed the orbital period value P orb  = 0.0545 ± 0.0026 d, consistent with early-superhump estimates, and the following orbital parameters: γ = −21 ± 3 km s −1 and K 1  = 53 ± 3 km s −1 . The white dwarf is revealed as the system approaches quiescence, which enables us to infer the effective temperature of the primary Teff  = 11 600 ± 400 K. The donor temperature is estimated ≲2200 K and suggestive of a system approaching the period minimum. Doppler maps in quiescence show the presence of the hotspot in He i line at the expected accretion disc-stream shock position and an unusual structure of the accretion disc in Hα.